Critical role of post-transcriptional regulation for IFN-γ in tumor-infiltrating T cells. (1st February 2019) - Salerno, Fiamma; Guislain, Aurelie; Freen-Van Heeren, Julian J.; Nicolet, Benoit P.; Young, Howard A.; Wolkers, Monika C.
ABSTRACT: Protective T cell responses against tumors require the production of Interferon gamma (IFN-γ). However, tumor-infiltrating T cells (TILs) gradually lose their capacity to produce IFN-γ and therefore fail to clear malignant cells. Dissecting the underlying mechanisms that block cytokine production is thus key for improving T cell products. Here we show that although TILs express substantial levels of Ifng mRNA, post-transcriptional mechanisms impede the production of IFN-γ protein due to loss of mRNA stability. CD28 triggering, but not PD1 blocking antibodies, effectively restores the stability of Ifng mRNA. Intriguingly, TILs devoid of AU-rich elements within the 3ʹuntranslated region maintain stabilized Ifng mRNA and produce more IFN-γ protein than wild-type TILs. This sustained IFN-γ production translates into effective suppression of tumor outgrowth, which is almost exclusively mediated by direct effects on the tumor cells. We therefore conclude that post-transcriptional mechanisms could be modulated to potentiate effective T cell therapies in cancer.